PENGARUH PENAMBAHAN TEPUNG UBI JALAR UNGU (Ipomea batatas L. var. ayamurasaki) TERHADAP KARAKTERISTIK HEALTH-PROMOTING YOGURT - Rizki, Gusti Chandra; Nocianitri, Komang Ayu; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p01, 2019)
This research aims to identify the effect of adding purple sweet potato flour to the characteristics of health-promoting yogurt and to identify the right concentration of purple sweet potato flour to produce health-promoting yogurt with the best characteristics. This research used a Randomized Block Design (RBD) of the addition of purple sweet potato flour with the concentration of 0%, 2%, 4%, 6%, 8%. Each treatment was repeated 3 times, resulting in 15 experimental units. The data were then Analyzed of Variance (ANOVA) method and if the treatment had an effect on the variable, the Duncan Multiple Range Test (DMRT) were performed. The results showed purple sweet potato flour has significant effect to lactic acid total, pH, antioxidant activity, color, texture, and taste of health-promoting yogurt and did not significantly affect LAB total, hedonic taste, aroma, and overall acceptance. The addition of 8% purple sweet potato flour resulted in the best characteristic under the following criteria: 1.23% of lactic acid total, 3.73 of pH, 90.33% of antioxidant activity, 13.19 log CFU/ml of LAB total, pink color and indefferent color, thick texture rather like, sour taste rather like, flavor and overall acceptance rather like. Keywords: health-promoting yogurt, purple sweet potato flour, antioxidant.